Acquired lymphangiectasis: A case report (major hallmarks in its differential diagnosis from lymphangioma circumscriptum) - (:unkn) unknown (My University, 2007)
Acquired lymphangiectasis is a superficial lymphatic dilatation caused by a wide range of scarring processes. Histologically indistinguishable from lymphangioma circumscriptum and commonly occurs in adults as a late sequel of surgery and radiation therapy. Patients usually present with numerous translucent vesicles in a chronic lymph edematous area several years after surgery with or without radiation therapy. We report a case of acquired lymphangiectasis, happened 17 years after the surgical intervention. Lesions were located the left subaxillary region. This is the first case that is reported so late in the literature after the surgery.
Keywords: Acquired; Lymphangiectasis; Lymphangioma circumscriptum